Relation between the Persistence of an Abnormal Muscle Response and the Long-Term Clinical Course after Microvascular Decompression for Hemifacial Spasm - TOBISHIMA, Hana (Neurol Med Chir (Tokyo), 2014)
Mentalis muscle responses to electrical stimulation of the zygomatic branch of the facial nerve are considered abnormal muscle responses (AMRs) and can be used to monitor the success of decompression in microvascular decompression (MVD) surgery. The aim of this study was to compare the long-term outcome of MVD surgery in which the AMR disappeared to the outcome of surgery in which the AMR persisted. From 2005 to 2009, 131 patients with hemifacial spasm received MVD surgery with intraoperative monitoring of AMR. At 1 week postsurgery, spasms had resolved in 82% of cases in the AMR-disappearance group and 46% of cases in the persistent-AMR group, mild spasms were present in 10% of cases in the AMR-disappearance group and 31% of cases in the persistent-AMR group, and moderate were present spasms in 8% of cases in the AMR-disappearance group and 23% of cases in the persistent-AMR group (P < 0.05). At 1 year postsurgery, spasms had resolved in 92% of cases in the AMR-disappearance group and 84% of cases in the persistent-AMR group, mild spasms were present in 6% of cases in the AMR-disappearance group and 8% of cases in the persistent-AMR group, and moderate spasms were present in 3% of cases in the AMR-disappearance group and 8% of the cases in the persistent-AMR group (P = 0.56). These results indicate that the long-term outcome of MVD surgery in which the AMR persisted was no different to that of MVD surgery in which the AMR disappeared.